Promotion of Healthy Lifestyles in the Elderly Integrated into an Active Aging Project in the Region of Tâmega and Sousa - João Rocha; Isabel Barroso; Ana Caramelo; Conceição Rainho (Medical Sciences Forum, 2023)
Demographic aging is a problem that affects the Portuguese population, and the forecasts for the coming years are not favorable. In the context of Master of Community Nursing, an internship was carried out in which health planning methodology was developed. Having diagnosed the situation, it was possible to identify the intervention needs at the level of lifestyle of the group of elderly who were part of an active aging project. To respond to the identified problem, an intervention project was implemented, with the activities aimed at promoting a healthy lifestyle.